PENGEMBANGAN ETIKA BISNIS SEBAGAI PROFESI LUHUR YANG BERKEMAJUAN - MOH. NASIKH (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
Ethics is a norm or a rule to regulate everything to make perfectness in a system, or a norm (a rule) is used as a guidance in applying or conducting of employees or someone (everyone) correlated with good or bad manners. This ethics is commonly used in a business or profession. The Implementation of this ethics which is named ‘ethic code’ has some goals, those are : stimulate moral awareness with its limitations for employers or entrepreneur to execute their businesses to get along with their visions and missions ; also improved and to make a good climate in their operations. To reach subtely professional business of course, it outlook must be broaden, not only realistic practice but must be idealistic one. Business is not only how to create profits, but how to server customers, because profits are only symbols of society trusts. It means, because the society or community feel their requirements well provided by the company, so they will like or prefer its product (service) well, beside that they are satisfied by them. To make the business subtlety and develop, the managers or employers should be getting along with ethics applied by some developed countries. They adapt and adopt some good total quality management by using 5 steps or concepts, are : (1) Continously Improvement (2) Empowering of Employee (3) Benchmarking (4) Just-in Time (5) Knowledge of tools.